Use of calcium hydroxyapatite and growth factors in endodontic therapy - Mitić, Aleksandar; Živković, Milan; Živković, Dušan; Popović, Lidija; Veličković, Zorana; Miladinović, Milan; Šubarić, Ljiljana; Marjanović, Dragan; Cvetković, Andrijana (Vojnosanitetski pregled, 2021)
Background/Aim. Hydroxyapatite (HAp)  is one of the most commonly used calcium phosphate bioceramics with osteoconductive properties. Growth factors are capable of directly inducing morphological and functional differentiation of neodontoblasts. The aim of this study  was to investigate the effectiveness of HAp-based biomaterial in combination with transforming growth factor-β1 (TGF-β1) in the creation of new dentine and obturation of the root canal apex in the teeth of an experimental animal model. Methods. Rodent (rabbit) teeth were used as the experimental animal model. After pulp removal with a pulp extirpator in vital pulpectomy, the biomaterial was applied using a Lentulo spiral in the apex portion at the level of the physiological foramen apicale. The experiment was performed in general anesthesia. Animals were kept alive for 3, 6, and 12 months after the treatment. The extracted teeth were analyzed by scanning electron microscopy (SEM). Results. Using SEM, it was found that the number of teeth with newly created dentine and apex canal obturation was greater 12 months after the treatment. Conclusion.  Apex obturation of the dental root canal with newly created dentine took place in our experimental groups treated by biomaterial with or without TGF-β1.
Keywords: odontoblasts; endodontics; dentin; biocompatible materials; transforming growth factors; tooth root; rabbits